Design and development of a prop-hanging mini aerial vehicle - Lee, Yuan Sheng. (2009)
A prop-hanging Unmanned Aerial Vehicle (PH-UAV) concept is designed and developed in the final year project. The PH-UAV is then fabricated and tested on its hovering capability. The completed PH-UAV prototype will be a good basis for further studies. This Final Year Report presents a PH-UAV design approach by first analyzing the theoretical aerodynamic properties followed by stability characteristics. The aerodynamic properties are analyzed through various programs and aerodynamic empirical models. These set the airfoil profile, aspect ratios, airfoil sweep and many other parameters through the comparison of lift, drag and moment coefficients. The power required also verifies the findings. These will be the basis for the structural design ideal for the hover flight for the PH-UAV. The stability analysis under hover flight condition is significantly different from that of horizontal flight in conventional aircraft, in which Euler angles involved in the transformations would give erroneous results. Thus, the stability of the PH-UAV are derived from the fundamental equations and manipulated differently for hover flight analysis. In between, assumptions relevant to hovering are applied. The set of stability modes, frequencies and roots derived are indicative of the stability of the PH-UAV. A clear understanding of stability theory and the mode of flight are required to perform various transformations correctly and the proper use of assumptions. The stability study determines the possible placements of CG and is a prediction of the likely stability behavior of the PH-UAV. After the Well detailed study in aerodynamics and stability, the PH-UAV is then fabricated in the lab. Hardware knowledge is required to put the various electronic systems together, such as the motors and transmitter-receiver system. Hands on technical skills are also needed to machine and fabricate various parts/mounts to attach the hardware on the structure. Practical technical knowledge is applied to determine the various positions of linkages and mounts such that these attachments required for remote operation do not affect the design of the prototype aerodynamically. Further work in the future will involve detailed analysis of the flight properties displayed during tests and how it deviates from the theoretical expectation. The theoretical model can be further modified to incorporate terms such that the actual behavior of the PH-UAV can be better reflected. Improvement on aerodynamic and stability properties can be made to enhance performance and endurance limits. Further hardware additions will be the integration of a control feedback system, an autonomous system and a camera system such that the prototype achieves good autonomous control with added surveillance ability.